The Impact of Energy Productivity and Eco-Innovation on Sustainable Environment in Emerging Seven (E-7) Countries: Does Institutional Quality Matter? - Safi, Adnan; Chen, Yingying; Zheng, Liya (Frontiers in Public Health, 2022)
Emerging economies are showing promising growth and economic success, but the growth process has significantly increased carbon emissions in these countries and deteriorated environmental quality. Environmental degradation is an issue of serious concern as it is directly linked to human lives and health. Since the creation of the Sustainable Development Goals (SDGs), the Emerging Seven (E-7) countries have struggled to meet the SDG targets, as it's been a challenge for them to lower carbon emissions and improve the quality of the environment. Thus, the present study explores the key factors that significantly affect environmental quality. This study examines the effect of institutional quality, energy productivity, and eco-innovation on consumption-based carbon dioxide (CCO2) emissions for E-7 economies. The cointegration analysis results showed a long-run relationship between institutional quality, energy productivity, GDP, eco-innovation exports, imports, and CCO2 emissions. The results obtained using the cross-sectionally augmented autoregressive distributed lag (CS-ARDL) model show that institutional quality, energy productivity, eco-innovation, and exports adversely affect CCO2 emissions and improve environmental quality in the short and long run. In contrast, imports and GDP are positively linked with CCO2 emissions and contribute to environmental degradation. Policies that target institutional quality, eco-innovation, and energy productivity significantly affect CCO2 emissions and help improve environmental quality.